FNAC of Head and Neck Lesions in a Tertiary Care Institute of Jammu- A 3 Year Retrospective Study - Deepti Gupta; Surbhi Mahajan; Anchal Gupta; Deepti Mahajan; Deepa Hans (Dr. Annil Mahajan, 2023)
Background: Head & neck region swellings are commonly encountered and rarely go unnoticed. FNAC provides early diagnosis and initial segregation into inflammatory versus neoplastic pathology. Aims & Objectives: To study the role of FNAC in head and neck lesions, to study the cytomorphological patterns of various head and neck lesions and to study the distribution according to age, sex and site of various head & neck lesions. Material & Methods: It is a retrospective observational study done over a period of 3 years from 1st May 2019 to 1st May 2022 in the Cytology section of the Post Graduate Department of Pathology in all age groups irrespective of their sex. Results: A total of 2024 cases of Head & neck region FNA (including guided FNA) aspirates were included in the study. Maximum number of cases were in the age group of 21-30 years (30%). Female to male ratio was 1.2:1 Maximum number of aspirates were from lymph nodes (41%) followed by thyroid (33%). In our study 68% cases were benign and 32 % cases were malignant. Conclusion: Our study shows patterns of head & neck lesions on FNAC. Despite its limitations FNAC still could be used as the initial investigating tool for assessing head & neck region swellings, although histopathology remains the gold standard.